Adnexal mass management in pregnancy: 50 Cases experience - Kavak, Salih Burçin; Çelik, Hüsnü; Gürateş, Bilgin; Çelik, Ebru; Baykuş, Yakup (Gunes Kitap Kirtasiye, 2012)
Purpose: Retrospective analysis of adnexal masses in pregnancy. Material and Method: We analysed the pregnancies who underwent treatment due to adnexal mass for the last five years in our clinic. From the archieve data, demographic properties of cases, pregnancy weeks, hystopathologic and perinatal results are obtained. Frozen section examination of materials sent from except the emergency situations. Postoperatively patients were evaluated close to tocolysis, and tocolysis were treated when necessary. Descriptive statistics were used to assess the data and variables used in % and the mean ± standard deviation. Findings: 16 cases underwent emergent operation due to torsion or abdominal bleeding. 11 cases were operated as elective, in 25 cases adnexal masses were diagnosed in cesarean section. 8% of the cases who were operated on first-trimester, 46% of the cases on second trimester, and again 46% of the cases on 3 trimester were. Mature cystic teratoma is the most common hystopathologic type of the adnexal masses diagnosed in pregnancy. Salpingooopherectomy unilateral adnexal masses in 3 cases underwent cystectomy was performed in all cases. Causes of gynecologic pelvic masses were detected except for two one case of mesenteric cyst, lipoma and the other were in favor. In two adnexal masses diagnosed incidentally in cesarean section, borderline ovarian tumor is diagnosed. None of the patients except two borderline tumors, malignant adnexal mass was detected. Results: It must be remembered in mind that adnexal masses can undergo regression in the first trimester and conservative management must be planned. In cases with high malignancy potential and in the case of rupture and torsion operation must be planned. Persistant adnexal masses must be extirpated in the second trimester between 14 and 22 week of pregnancy.
Gebelikte adneksiyel kitle yönetimi: 50 olgu deneyimi
Keywords: Mature cystic teratoma; Ovarian cysts; Pregnancy